The internal marketing in the last decade : A systematic review - Musa, Abubakar; Ijaiya , Dr. Mukaila Adebisi; Umaru Mustapha, Zubairu (IROCAMM - International Review Of Communication And Marketing Mix, 2021)
This research examines internal marketing (IM) over the last decade (2012-2021) using systematic quantitative assessment techniques (SQAT). The review identified 82 IM articles from 39 countries. A significant number of the articles were published in 2015, with a large concentration in Asia. The majority of the articles reviewed were empirical research. Four methods of data collection (i.e. survey, Secondary data, interview, and observation) were identified. The review identified three different IM themes (i.e. IM magnitude, consequences of IM, and IM mechanism). This review recommends that more IM articles are encouraging in South America and other nations of other countries that currently have no representation. More conceptual research is encouraged in balancing the wide gap between empirical and conceptual articles. Researchers are encouraged to use more qualitative methods of data collection to gain more understanding of the concept. The researchers are also advised to adopt the mixed method of data collection on the consequences of IM and IM mechanisms themes.